Pengaruh Capital Intensity, Inventory Intensity dan Leverage Terhadap Tax Avoidance dengan Komite Audit Sebagai Variabel Moderasi - Septiana, Andini Agustiyas; Venusita, Lintang (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The Tax Justice Network (2024) reported that Indonesia loses approximately US$2.98 billion annually due to corporate tax avoidance practices. This condition indicates that tax avoidance remains an issue that requires serious attention. This study aims to examine the effect of capital intensity, inventory intensity, and leverage on tax avoidance, with the audit committee serving as a moderating variable. This study employed a quantitative approach using secondary data in the form of annual financial statements. The research sample consisted of 61 manufacturing companies in the consumer non-cyclicals subsector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, resulting in a total of 183 observations selected through purposive sampling. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews version 13 software. The results indicate that capital intensity has a significant effect on tax avoidance, while inventory intensity and leverage have no effect on tax avoidance. In addition, the audit committee is unable to moderate the effect of capital intensity, inventory intensity, and leverage on tax avoidance. Future research is recommended to include additional variables that may influence tax avoidance and extend the observation period to obtain more comprehensive findings.